The effect of rapid weight loss on sports injury in elite taekwondo athletes - Kim, H. C.; Park, K. J. (The Physician and Sportsmedicine, 2023)
Objectives The purpose of this study was to reveal the relationship of injury patterns between normal training period and weight loss period in Korea elite taekwondo athletes.